Determinan Sosial Ekonomi Rumah Tangga dari Balita Stunting di Indonesia: Analisis Data Indonesia Family Life Survey (IFLS) 2014 - Indrastuty, Dini; Pujiyanto, Pujiyanto (UI Scholars Hub, 2018)
Stunting is a chronic nutritional problem in infants characterized by shorter stature compared to their age. Stunting in toddlers has risk at the level of intelligence, vulnerability to disease, lowering productivity which in the long run can hamper economic growth. When adults, children who suffer from stunting are prone to non-communicable diseases. This causes government spending in terms of financing national health insurance to continue to increase. This study aims to analyze the determinants of household socioeconomic factors of stunting toddlers. It used the secondary data of the Indonesian Family Life Survey (IFLS) in 2014 with cross-sectional study design and the application of an econometric logit model. The number of observations as a sample in this study amounted to 3,794 toddlers on a national scale. The results showed the incidence of stunting toddlers had a significant relationship with the employment status of mothers, shelter, sanitation and economic status. Mothers who spend more time and pay attention to child nutrition, toddlers who can reach health care facilities, access to good sanitation, family economic status, proper government intervention, and the role of cross-sector and community order have an impact on the handling of stunting problems in Indonesia